A window into the Early to mid‐Cretaceous infrastructure of the Yukon‐Tanana terrane recorded in multi‐stage garnet of west‐central Yukon, Canada. (8th July 2013) - Staples, R. D.; Gibson, H. D.; Berman, R. G.; Ryan, J. J.; Colpron, M.
Abstract: Amphibolite facies metasedimentary schists within the Yukon‐Tanana terrane in the northern Canadian Cordillera reveal a two‐stage, polymetamorphic garnet growth history. In situ U‐Th‐Pb Sensitive High Resolution Ion Microprobe dating of monazite provide timing constraints for the late stages of garnet growth, deformation and subsequent decompression. Distinct textural and chemical growth zoning domains, separated by a large chemical discontinuity, reveal two stages of garnet growth characterized in part by: (i) a syn‐kinematic, inclusion‐rich stage‐1 garnet core; and (ii) an inclusion‐poor, stage‐2 garnet rim that crystallized with syn‐ to post‐kinematic staurolite and kyanite. Phase equilibria modelling of garnet molar and compositional isopleths suggest stage‐1 garnet growth initiated at ~600 °C, 8 kbar along a clockwise P–T path. Growth of the compositionally distinct, grossular‐rich, pyrope‐poor inner portion of the stage‐2 overgrowth is interpreted to have initiated at higher pressure and/or lower temperature than the stage‐1 core along a separate P–T loop, culminating at peak P–T conditions of ~650–680 °C and 9 kbar. Stage‐2 metamorphism and the waning development of a composite transposition foliation (ST ) are dated at c . 118 Ma from monazite aligned parallel to ST, and inclusions in syn‐ to post‐ST staurolite and kyanite. Slightly younger ages ( c . 112 Ma) are obtained from Y‐rich monazite that occurs within resorbed areas of both stage‐1 and stage‐2 garnet, together with retrograde staurolite and plagioclase. The younger ages obtained from these texturally and chemically distinct grains are interpreted, with the aid of phase equilibria calculations, to date the growth of monazite from the breakdown of garnet during decompression at c . 112 Ma. Evidence for continued near‐isothermal decompression is provided by the presence of retrograde sillimanite, and cordierite after staurolite, which indicates decompression below ~4–5 kbar prior to cooling below ~550 °C. As most other parts of the Yukon‐Tanana terrane were exhumed to upper crustal levels in the Early Jurassic, these data suggest this domain represents a tectonic window revealing a much younger, high‐grade tectono‐metamorphic core (infrastructure) within the northern Cordilleran orogen. This window may be akin to extensional core complexes identified in east‐central Alaska and in the southeastern Canadian Cordillera.